2015 IEEE 21st International Symposium for Design and Technology in Electronic Packaging (SIITME) 2015
DOI: 10.1109/siitme.2015.7342293
|View full text |Cite
|
Sign up to set email alerts
|

Investigating mechanical performance of PLA and CA biodegradable printed circuit boards

Abstract: Abstract-The paper presents a set of experiments investigating the mechanical performance of PCBs manufactured from biodegradable, sustainable polymers, compared to conventional materials. Cellulose Acetate (CA), Polylactic Acid (PLA) and FlameRetardant Class 4 (FR-4) substrates were compared during the experiments. The methods involved dynamic mechanical analysis (DMA), three-point bending tests and UL 94 flammability tests. Preliminary results show that the overall performance of the basic biodegradable, sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…These research groups focused on miscibility, thermal behavior, mechanical properties, interfacial compatibility of different blends and the effects on crystallization of PLA. Mahanwar et al [14] studied on the network formation in microcrystalline cellulose and PLA with similar investigations as previous researchers [8][9][10][11][12][13]. A number of groups concluded that there was a possibility of blending different polymers with PLA to yield enhanced thermal and mechanical properties, however, some studies reported negative results on miscibility for polymer blends [11] and matrix adhesion [14] for cellulose-PLA interaction.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…These research groups focused on miscibility, thermal behavior, mechanical properties, interfacial compatibility of different blends and the effects on crystallization of PLA. Mahanwar et al [14] studied on the network formation in microcrystalline cellulose and PLA with similar investigations as previous researchers [8][9][10][11][12][13]. A number of groups concluded that there was a possibility of blending different polymers with PLA to yield enhanced thermal and mechanical properties, however, some studies reported negative results on miscibility for polymer blends [11] and matrix adhesion [14] for cellulose-PLA interaction.…”
Section: Introductionmentioning
confidence: 72%
“…Novel approaches have been investigated to enhance the limiting properties of PLA for high performance applications. Blending of PLA with other polymers have been reported by a number of researchers [8][9][10][11][12][13]. These research groups focused on miscibility, thermal behavior, mechanical properties, interfacial compatibility of different blends and the effects on crystallization of PLA.…”
Section: Introductionmentioning
confidence: 99%
“…The main concern of those biopolymers is to improve their characteristic profile to reach that of standard materials. Like Géczy et al [4] stated PLA has to be modified with additives. Therefore this paper deals with PLA mixed with different contents of cellulose acetate and zinc pyrophoshate (ZnPP).…”
Section: Introductionmentioning
confidence: 98%
“…Our previous work focused on PLA with different contents of cellulose acetate (CA) and aluminum polyphosphate and found out that it is critical to use conductive pastes because of the thermal stress [2,3]. Géczy et al [4] investigated the mechanical performance of pure PLA and cellulose acetate. They found out that both materials act weaker than standard materials and that additives are needed to improve the mechanical performance.…”
Section: Introductionmentioning
confidence: 99%
“…The use of PCBs in electronic devices usually sets specific requirements for surface roughness and adhesion, mechanical durability, temperature stability and moisture tolerance; the use of fire retardants is also often expected [ 14 , 15 , 18 , 19 ]. The capability of wood-based materials to meet these expectations might be limited, but the work reported in this paper aims to show that there are potential material alternatives already available which are compatible with electronic performance and printability requirements.…”
Section: Introductionmentioning
confidence: 99%